Model-model Pembelajaran Passing Bawah Dalam Permainan Bola Voli - Bara, Fabianus Kalikit; Martin Siahaan, Jurdan; Runesi, Salmon (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2024)
ABSTRACT Background Volleyball games are a form of effort or activity that is carried out effectively and continuously to achieve optimal results, which include physical, tactical, technical and mental training patterns. One of the volleyball games is bottom passing. Purpose of the study This study is to determine the Learning Models of Bottom Passing in Volleyball Games in Students of SD Inpres Oepura 2 Kupang, Maulafa District. Research method This study uses qualitative descriptive methods with data collection techniques used, namely observation, interviews, and documentation as well as data analysis techniques in this study, namely data reduction, data presentation, and conclusions. The sample in this study is how teachers provide techniques, tactics and exercises to develop bottom passing in the game of volleyball. Results and discussion Primary data sources are obtained from direct interviews with teachers and students. The causes of decreased bottom passing are lack of practice done by students, lack of anticipation from students about practice techniques, students never do independent exercises at home so that it can hurt the decline of bottom passing in volleyball games. It is concluded that studets are expected to focus on the direction or criteria from the teacher so that it becomes a benchmark for determining student motivation in performing lower passes.